Phenol tert-butylation over zirconia-supported 12-molybdophosphoric acid catalyst - Devassy, Biju M.; Shanbhag, G.V.; Halligudi, S.B. (Journal of Molecular Catalysis A-Chemical, 2006)
The alkylation of phenol with tert-butanol was investigated using zirconia-supported 12-molybdophosphoric acid (MPA) as catalyst. The catalysts with different MPA loading (5-25 wt.% calcined at 700 degrees C) and calcination temperature (15 wt.% calcined from 500 to 750 degrees C) were prepared by suspending zirconium oxyhydroxide in methanol solution of MPA followed by drying and calcination. These catalysts were characterized by X-ray diffraction and (31)p MAS NMR spectroscopy measurements. The XRD results indicated that MPA stabilizes the tetragonal phase of zirconia. (31)p MAS NMR spectra showed the presence of three types of phosphorous species, phosphomolybdate in interaction with zirconia, decomposition product of MFPA and an unidentified species. IFTIR pyridine adsorption on 15% MPA catalyst calcined at different temperatures showed the presence of both Bronsted and Lewis acidity and the catalyst calcined at 700 degrees C showed the highest relative Bronsted acidity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), the phenol conversion was 80.6% at 2 h (selectivity to 2-TBP 11.5%, 2,4-DTBP 55.2%, and 4-TBP 25.7%), which decreased slowly with time and at 31 h, it was 58.5% (selectivity to 2-TBP 15.2%, 2,4-DTBP 41.6%, and 4-TBP 38.4%). The major reason for the catalyst deactivation was the reduction and leaching of MPA from the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 12-molybdophosphoric acid; phenol; tert-butylation; Zirconia